Development and Validation of a Brief Instrument to Evaluate Primary-Care AMI Management in Mexico - Quiroz-Gomez, Sergio; Salgado-Montalvo, Juvenal Eduardo; Baños-González, Manuel Alfonso; Solís-Montero, Jesús Arturo; Celorio Méndez, Karla del Socorro; Chale-De la Cruz, Alejandro Ernesto; Guzmán Priego, Crystell Guadalupe; Jiménez-Sastré, Alejandro; Moreno, Marisol Guzmán (International Journal of Statistics in Medical Research, 2025)
This descriptive cross-sectional study developed and validated an instrument to evaluate the initial management of acute myocardial infarction (AMI) at the primary-care level in Mexico. The instrument was constructed from the Mexican Social Security Institute Infarction Code and the national Clinical Practice Guideline, extracting core elements for first-contact AMI care. Expert judgment guided item selection using the Rovinelli and Hambleton approach, and items with Aiken’s index ≥0.70 were retained. A pilot test with 35 primary-care physicians assessed the preliminary version. The field sample comprised 143 physicians from the 17 municipalities of Tabasco, selected by convenience sampling. Reliability was estimated with Cronbach’s alpha. The pilot version showed α=0.636; after expert validation and refinement—including the addition of two items (on fibrinolytic dosing in adults ≥75 years and post-fibrinolysis protocol)—the final 10-item instrument achieved α=0.817. Corrected item–total correlations improved notably for item 2 (from 0.243 to 0.544), while items 5 and 8 showed the highest values in the final version. Factorability was adequate (KMO = 0.736; Bartlett’s χ²(36) = 83.609, p < 0.001). This brief, context-specific tool shows solid internal consistency and expert-supported content validity for primary-care AMI management; structural and criterion (predictive) validity should be further confirmed.